Phraseological Units with Zoomorphic and Somatic Components: A Contrastive Approach - Lepojević, Jelena B.; Nikolić, Emilija G. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
This paper is based on two fundamental premises. First, phraseology serves as an indispensable source for reconstructing the linguistic worldview, revealing the mechanisms of our conceptual system as well as the beliefs and symbols embedded in cultural consciousness. Second, animals, as an inseparable part of human experience, provide a rich basis for the metaphorical depiction of human traits. Accordingly, the study focuses on a specific stratum of phraseological units in Russian and Serbian: comparative phraseological units with a zoomorphic component and phrasemes containing somatisms.The central research question addresses the relationship between these two related yet formally distinct constructions. The aim is to determine to what extent and under what conditions a functional overlap occurs between comparative phraseological units with zoomorphisms (e.g., храбар као лав / храбрый как лев) and phrasemes with somatisms (e.g., лавље срце / львиное сердце), and whether a semantic distinction exists between them that reflects subtler nuances in the linguistic conceptualization of these notions. Through a contrastive approach, the study provides insight into the similarities and differences in the perception of animals and bodily metaphors within the two Slavic linguistic and cultural traditions. In addition to semantic analysis, the study examines phraseological units from typological and structural-component perspectives.
Keywords: phraseology; comparative phraseological units; somatisms; zoomorphisms; comparative–contrastive analysis; Russian; Serbian